If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3y+6=5y=2
We move all terms to the left:
3y+6-(5y)=0
We add all the numbers together, and all the variables
-2y+6=0
We move all terms containing y to the left, all other terms to the right
-2y=-6
y=-6/-2
y=+3
| 3(y+2)=5y=2 | | 59x+4=180 | | X^5(x=3)+2(x+3) | | 4p+2/3=6 | | -3x+16=-1x | | 10x+25(14-x)=275 | | x2+7x+10=130 | | m^2-1m-42=0 | | 3-1x=-5-1x | | 576+24x=324+18x | | 190=6x-11 | | 6(y+97)-89=-83 | | 16+4x=36+6x | | 2x^2−20=97−x^2 | | 2x2−20=97−x2 | | 3x+6=4+9 | | 2(12+x)=2x+14 | | 7x=-3+23 | | 21/2(3-w=w+9 | | 2x-57+x=90 | | 3m-9=-10 | | b/11=-6 | | -7-m=-24 | | 5x+10=2x+24 | | 3(y-7)=-57 | | 48x^2-49x+12=0 | | 3(y-21)=-57 | | 17n-23n+11.n=44 | | -1.7x=9(x+2.14) | | 2(5x-3)+1=4(x+5)+6 | | 4x+15=5x-2 | | 5x-8+3(2x-5)=0 |